A Brief Analysis of Guilin Baptist (Zion) Hospital - JIA Xiao, (Journal of Research for Christianity in China (JRCC), 2025)
Christian medical missions in China constituted a vital component of modern Christian missionary endeavors, undergoing a prolonged process of development and transformation throughout modern Chinese history. Following Christianity's introduction to China, numerous church-affiliated hospitals were established, exerting significant influence on modern Chinese healthcare and directly or indirectly propelling China's modernization. Guilin Baptist (Zion) Hospital exemplifies such a modern church-affiliated institution. Established in 1916, it weathered multiple waves of anti-Christian sentiment, endured the devastation of wartime bombardment during the War of Resistance Against Japan, and underwent restructuring and mergers during the Liberation War era. After several name changes, it evolved into today's Guilin Second People's Hospital. Despite its turbulent founding and development, the hospital's fundamental purpose of “medical missionary service” remained unchanged during its ecclesiastical period. Like other church hospitals, it bore the attribute of cultural influence. Yet over decades, it played a vital role in introducing Western medicine and pharmaceuticals, training medical and nursing professionals, and participating in medical aid and local social services. Objectively, it advanced the progress and development of modern healthcare in Guilin. Guilin Baptist (Zion) Hospital stands as a mirror reflecting history. Weathering unpredictable social upheavals, enduring wars with resilience and vigilance, it was destroyed multiple times only to be rebuilt, encapsulating decades of Guilin's development and transformation. Tracing its history provides clearer insight into the humanitarian endeavors of Guilin Baptist (Zion) Hospital, illuminates the developmental shifts in modern Guilin society, advances research on Guilin's church history, and deepens understanding of Guilin's historical and cultural legacy. The evolution of Guilin Baptist (Zion) Hospital demonstrates that modern church-affiliated hospitals represented a distinct form of missionary endeavor. Medical missionaries initially pursued healthcare as a means to evangelize, making medical work fundamentally a tool for proselytizing. However, the distinct nature of the medical professions—doctor and nurse—led these missionaries to prioritize patient care during medical activities. This professional ethos made them resemble physicians and nurses more than missionaries. Particularly in the process of treating patients, medical missionaries provided spiritual comfort, integrating physical healing with emotional care. Even when Christian beliefs were mentioned during treatment, their willingness to treat patients remained unchanged regardless of the patient's religious affiliation. The conduct of medical workers in modern church hospitals embodied both compassion and skill. While the primary purpose of modern missionaries coming to China was evangelism, the doctors and nurses who arrived generally lacked the fervent missionary zeal of their fellow missionaries. Their primary identity was as medical professionals, whose highest calling was to use their skills to alleviate human suffering. Their national affiliation served merely as an identity marker. Since their countries entrusted them with missionary tasks, certain evangelistic elements were incorporated into patient care. This approach ensured hospitals could operate sustainably with financial and organizational support from Christian churches. While some church-affiliated hospitals provided free or minimal-cost treatment, the religious affiliation of patients was irrelevant. Whether patients converted to Christianity through baptism after recovery was not a consideration for physicians. Particularly since the 19th century, the majority of medical missionaries arriving in China came from commoner and middle-class backgrounds. Through their aid, patients recovered and, through their own efforts, brought medical assistance to broader regions. Building upon existing research and utilizing collected archival materials, this thesis provides a comprehensive and systematic review of the history of Guilin Baptist (Zion) Hospital to explore the relationship between modern church hospitals and local society. The article is structured into seven sections: Part One, the Introduction, outlines the research objectives, rationale, and significance, while reviewing existing studies on Guilin Baptist (Zion) Hospital. Part Two briefly details the hospital's founding context, identifying the local social environment of early 20th-century Guilin, the arrival of churches in Guilin, and their medical missionary work as key internal and external factors. Part III outlines the developmental trajectory of Guilin Baptist (Zion) Hospital, covering three historical phases: its initial establishment, the period of destruction, and its subsequent reconstruction and expansion. Part IV examines the hospital's administrative structure and operational mechanisms. Part Five clarifies the hospital's primary activities, including religious affairs, medical services, charitable work, and public welfare initiatives. Part Six objectively summarizes and analyzes the hospital's key characteristics and historical significance. Part Seven concludes by succinctly highlighting the dual nature of Guilin Baptist (Zion) Hospital as both a medical institution and a missionary outpost.